Perawatan Saluran Akar dengan Teknik Step Back pada Gigi Depan Atas Sebelah Kanan : Laporan Kasus: Root Canal Treatment with Step Back Technique on the Right Upper Front Tooth : A Case Report - Chanal, Izzati Chatyarianti; Nurdin, Denny (Bhakta Dental Journal, 2025)
Root canal treatment is a procedure to remove the infected pulp tissue from the tooth, then clean, fill, and seal it. The main steps are access preparation, cleaning and shaping, and obturation. One of the cleaning and shaping method is the step-back technique. This technique is the conventional technique performed by preparing the apical portion first. Step-back technique have its advantages such as more flaring in the coronal portion and more precise apical stop. This case report describes a 52-year-old male patient who came with a cavity in the upper right front tooth, the patient had felt a spontaneous pulses for one year, but the intensity had decreased. Radiographic examination showed the condition of the horizontal bone loss approximately 2 mm in the alveolar bone, periodontal ligament widening, and the lamina dura was discontinuity in the apical third. The diagnosis was made as symptomatic irreversible pulpitis with symptomatic apical periodontitis of tooth 13, and the treatment plan was root canal treatment. The treatment begins with caries removal, access opening, extirpation, and re-walling. On the second visit working length determination, root canal preparation using the step-back technique, administration of medicament. On the next visit the root canal was filled and closed with a temporary filling, and the root canal treatment of tooth 13 showed a good results.